B cell zone reticular cell microenvironments shape CXCL13 gradient formation - Cosgrove, Jason; Novkovic, Mario; Albrecht, Stefan; Pikor, Natalia B.; Zhou, Zhaoukun; Onder, Lucas; Mörbe, Urs; Cupovic, Jovana; Miller, Helen; Alden, Kieran; Thuery, Anne; O’Toole, Peter; et al. (Nature communications, 2020)
Through the formation of concentration gradients, morphogens drive graded responses to extracellular signals, thereby fine-tuning cell behaviors in complex tissues. Here we show that the chemokine CXCL13 forms both soluble and immobilized gradients. Specifically, CXCL13 + follicular reticular cells form a small-world network of guidance structures, with computer simulations and optimization analysis predicting that immobilized gradients created by this network promote B cell trafficking. Consistent with this prediction, imaging analysis show that CXCL13 binds to extracellular matrix components in situ, constraining its diffusion. CXCL13 solubilization requires the protease cathepsin B that cleaves CXCL13 into a stable product. Mice lacking cathepsin B display aberrant follicular architecture, a phenotype associated with effective B cell homing to but not within lymph nodes. Our data thus suggest that reticular cells of the B cell zone generate microenvironments that shape both immobilized and soluble CXCL13 gradients. Morphogens such as chemokines form gradients to direct graded responses and modulate cell behaviors. Here the authors show, using imaging and computer simulation, that the chemokine CXCL13 originated from follicular reticular cells in the lymph nodes forms both soluble and immobilized gradients to regulate B cell recruitment and migration.